2015
DOI: 10.1007/s00382-014-2461-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictability and prediction skill of the boreal summer intraseasonal oscillation in the Intraseasonal Variability Hindcast Experiment

Abstract: ratio method and using ensemble-mean approach, we found that the multi-model mean BSISO predictability estimate and prediction skill with strong initial amplitude (about 10 % higher than the mean initial amplitude) are about 45 and 22 days, respectively, which are comparable with the corresponding counterparts for Madden-Julian Oscillation during boreal winter (Neena et al. in J Clim 27:4531-4543, 2014a). The significantly lower BSISO prediction skill compared with its predictability indicates considerable ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 60 publications
5
50
0
Order By: Relevance
“…While model deficiencies in depicting cumulus processes are generally blamed to be responsible for model inability to represent the MJO, essential MJO physics and key model processes for its realistic simulations are still elusive. Motivated by a longstanding and urgent need to improve the MJO in current weather forecasting and climate models, the MJO has been a central focus of several recent international projects in the tropical climate research community [ Zhang et al ., ], including the Intraseasonal Variability Hindcast Experiment [ Neena et al ., ; Lee et al ., ], the Year of Tropical Convection (YOTC) virtual field campaign [ Moncrieff et al ., ; Waliser et al ., ], the Cooperative Indian Ocean Experiment on Intraseasonal Variability (CINDY2011) and Dynamics of the MJO [ Yoneyama et al ., ], and the project on Subseasonal to Seasonal Prediction [ Vitart et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…While model deficiencies in depicting cumulus processes are generally blamed to be responsible for model inability to represent the MJO, essential MJO physics and key model processes for its realistic simulations are still elusive. Motivated by a longstanding and urgent need to improve the MJO in current weather forecasting and climate models, the MJO has been a central focus of several recent international projects in the tropical climate research community [ Zhang et al ., ], including the Intraseasonal Variability Hindcast Experiment [ Neena et al ., ; Lee et al ., ], the Year of Tropical Convection (YOTC) virtual field campaign [ Moncrieff et al ., ; Waliser et al ., ], the Cooperative Indian Ocean Experiment on Intraseasonal Variability (CINDY2011) and Dynamics of the MJO [ Yoneyama et al ., ], and the project on Subseasonal to Seasonal Prediction [ Vitart et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…They found that useful probabilistic forecasts could be generated up to the fourth pentad lead. Lee et al (2015) examined the predictability and prediction skill of BSISO over the ASM region in the IntraSeasonal Variability Hindcast Experiment (ISVHE). They found the multi-model mean BSISO predictability and prediction skill with strong initial amplitude (10% higher than the mean initial amplitude) are about 45 and 22 days, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction skills for the first two leading modes have increased from 7 days during 1990s to about 25-30 days (ECMWF and GFDL models) during 2010s (Vitart 2014;Xiang et al 2015). However, the models still have large room to reach potential predictability limit (Neena et al 2014;Lee et al 2015). Realistic simulation of MJO in many current general circulation models (GCMs) remains a great challenge .…”
Section: Introductionmentioning
confidence: 99%